Promosi Gizi Bayi Balita Bagi Orang Tua Anak Penderita Stunting di Puskesmas Alak Kota Kupang Tahun 2022 - Loriana L. Manalor; Martina F. Diaz; Jane A. Peni (Jurnal Health Sains, 2022)
Background Health development as part of efforts to build a whole person, (1) Children are the nation's assets in the future. Health efforts that are carried out since the child is still in the womb until the first five (5) years of life are aimed at maintaining their survival while at the same time improving the quality of life of the child. (2) The role of parents is very important in fulfilling nutrition because at this time children really need attention and care. parental support in the face of very rapid growth and development. (3) One of the health indicators that is assessed for its successful achievement in the Sustainable Development Goals (SDG's) is to find sustainable solutions to end hunger and all forms of malnutrition and to achieve food security by 2030. (4) The problem of stunting nutrition will have an impact on cognitive abilities , long term productivity. (5) Nutritional problems, especially for toddlers who suffer from stunting, can hinder the growth and development process of toddlers. Stunting is a chronic nutritional problem in toddlers which is characterized by a shorter height compared to children his age. The problem of short toddlers illustrates the existence of chronic nutritional problems that are influenced by the condition of the mother/prospective mother, fetal period, and infancy/toddler, including diseases suffered during infancy and other problems that indirectly affect health. (9) Short and very short or what is often referred to as stunting is a nutritional status based on a height index for age. The percentage of very short and short toddlers aged 0-59 months in Indonesia in 2018 was 11.5% and 19.3%, respectively. Objective To improve the ability of parents in promoting nutrition for infants under five for parents with stunting at the Alak Health Center, Kupang City in 2022. The method used in this study was quantitative with a quasi-experimental method with a research design of One group pretest posttest design, namely a research design that included a pretest before given treatment and posttest after being given treatment. The research subjects were all parents of infants under five in the working area of the Alak Public Health Center, Kupang City.